Crystallographic study of plasticity and grain boundary separation in FeCo alloy using small single- and bi-crystalline specimens. (1st January 2018) - Kishi, Daichi; Mayama, Tsuyoshi; Mine, Yoji; Takashima, Kazuki
Abstract: To study the relationship between the plasticity and intergranular fracture of FeCo intermetallic alloys, small, single- and bi-crystalline specimens were subjected to micro-tensile testing and crystal plasticity finite element analyses. The single-crystalline specimens exhibited a high strength and a large strain-to-failure compared with the bi-crystalline and polycrystalline specimens. The critical resolved shear stress for the {1 1 ¯ 0} 〈111〉 slip was ~ 100 MPa. For the bi-crystalline specimen, the intergranular fracture was determined by stress concentration due to the difference in the strain between the deformed and undeformed crystals. Graphical abstract: